First person - Phillipe O'Brien (The Company of Biologists, 2018)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms (DMM), helping early-career researchers promote themselves alongside their papers. Phillipe O'Brien is first author on 'Juvenile murine models of prediabetes and type 2 diabetes develop neuropathy', published in DMM. Phillipe is a Postdoctoral Researcher in the lab of Dr Eva Feldman at the University of Michigan, Ann Arbor, MI, USA, investigating the use of mouse models of disease to understand the development of peripheral neuropathy, a common complication of obesity, prediabetes and type II diabetes.